The Impact of Authoritative Parenting Patterns on the Social-Emotional Development of Early Childhood in Indonesia - Setyaningsih, Diana; Mamma, Agustinus Tandilo; Olua, Erna; Sirjon, Sirjon (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
Parenting patterns play a crucial role in shaping the social-emotional development of children, particularly during early childhood, a formative period for emotional and social skills. Among various parenting styles, authoritative parenting has been widely recognized for promoting positive child outcomes, including better social-emotional development. In Indonesia, cultural norms and family dynamics can influence how parenting styles are applied, making it important to explore how authoritative parenting specifically affects young children’s emotional regulation, empathy, and social interactions. This study aims to examine the impact of authoritative parenting on the social-emotional development of early childhood in Indonesia. A mixed-methods approach was used, combining quantitative surveys with qualitative interviews. The study involved 200 parents and their children aged 3-6 years, assessing parenting styles through the Parenting Style Inventory and evaluating children’s social-emotional development using established scales for emotional regulation, peer relationships, and social competence. The results indicate that children raised by authoritative parents displayed higher levels of emotional regulation, empathy, and peer acceptance compared to children raised by permissive or authoritarian parents. The study concludes that authoritative parenting is positively associated with enhanced social-emotional skills in early childhood and emphasizes the importance of promoting authoritative parenting practices in Indonesia to foster healthier developmental outcomes.